Convex fragmens of strongly minimal Jonsson sets - Yeshkeyev, A.R. (KSU publ., 2015)
This article introduced and discussed the concepts of minimal Jonsson sets and respectively strongly minimal Jonsson sets. On this basis, we introduce the concept of independence of special subsets of existentially closed submodel of semantic model. The concept of independence leads to the concept of basis and then we have the Jonsson analogue of the theorem on uncountable categoricity.
Қатты минималды йонсондық жиындардың дөңес фрагменттері
Выпуклые фрагменты сильно минимальных йонсоновских множеств
Keywords: Jonsson sets; Jonsson strongly minimal sets; fragments of Jonsson sets